Outcome of active TB case finding among a nomadic population in Nigeria - S. Gande; C. Ogbudebe; B. Odume; O. Chukwuogo; J. Emefieh; A. Babayi; A. Yakubu; S. John; S. Abdulkarim (Public Health Action)
SETTING: Finding TB among nomads, a high-risk group, can help address the global challenge of missing TB cases. Nigeria accounts for 6.2% of the 3.1 million missing TB cases. OBJECTIVE: To describe the outcome of active TB case-finding (ACF) among nomads in Bauchi State, northeastern Nigeria. DESIGN: KNCV implemented ACF in eight Local Government Areas of Bauchi State from June 2020 to December 2023. Trained community volunteers screened nomads and ensured diagnostic testing of sputum samples of nomads with presumptive TB. Community volunteers helped to link those with confirmed TB to treatment. RESULTS: We screened 43,070 nomads (35,533 adults; 7,537 children) of which 43% were males. Presumptive TB was detected among 12,387, of whom 850 (6.9%) had active TB, including 61 children. Overall, 99% of people with active TB were put on treatment. Presumptive TB yield was higher among the nomads, but active TB yield was comparable with the general population. Nomads contributed 5% to the total number of people notified with TB from Bauchi State. CONCLUSION: ACF among nomads resulted in improved TB notification and can help improve the identification of missing TB cases in Nigeria.